Phylum Tardigrada Doyère, 1840. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Guidetti, Roberto; Bertolani, Roberto (Zootaxa, 2011)
-